Studi Deskriptif Kuantitatif tentang Kualitas Tidur Pecandu Rokok - Diva Ingriani; Aulia Aisha Nadhirah; Hanisa Azura; Syahidah Alifia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to describe the quality of sleep in cigarette addicts, especially among young adults aged 18-24 years. Smoking, which has become a habit for many individuals, can cause dependence, one of which is caused by nicotine which disrupts sleep quality. Based on WHO data (2015), Indonesia is one of the countries with the largest number of smokers in the world, which has an impact on physical and psychological health, including sleep disorders. This research used a quantitative approach with descriptive methods and survey techniques by distributing The Pittsburgh Sleep Quality Index (PSQI) questionnaire to 12 respondents. The results showed that 100% of respondents experienced poor sleep quality, with the majority experiencing sleep disturbances less than once a week and daytime activity dysfunction more than three times a week. This research confirms the relationship between cigarette addiction and poor sleep quality in young adults. Based on these findings, it is recommended that smokers avoid nicotine before bed, establish a regular sleep schedule, and create a relaxing sleep routine to improve the quality of their sleep.